ANALYZING THE USE OF ARTIFICIAL INTELLIGENCE (AI) IN WRITING ACADEMIC PAPERS OF STUDENT AT UNIVERSITAS PGRI PALEMBANG - Ridho, M.; Jaya, Aswadi; Hermansyah; Suthida Chantavhong; Nattapong Rattanakosin (Esteem Journal of English Education Study Programme, 2025)
This study investigates the role of Artificial Intelligence (AI) in enhancing students’ academic writing skills, with a specific focus on English Education students at Universitas PGRI Palembang. Utilizing a qualitative descriptive design within a phenomenological framework, the research examines the impact of AI tools—such as ChatGPT, Grammarly, and Quillbot—on the quality of student writing, their knowledge development, and their perceptions of these technologies. Data were gathered through observations, interviews, and documentation involving 10 students from the second and fourth semesters. The results indicate that AI tools play a significant role in helping students generate ideas, refine grammar and structure, and increase overall writing efficiency. Nevertheless, the study also uncovers ethical challenges, including dependency on AI and risks of plagiarism. In general, students expressed favorable views of AI, considering it a beneficial aid rather than a substitute for critical thinking. The study emphasizes the importance of integrating AI in a balanced way to preserve originality, foster creativity, and uphold academic integrity.